A NOVEL SIGNAL PROCESSING METHOD BASED ON FREQUENCY MODALITY FOR INTRA-BODY MEDICAL INSTRUMENT TRACKING - Fotiadis, Dimitrios A.; Papathanasiou, Kostas; Astaras, Alexandros; Bamidis, Panagiotis D.; Kalfas, Anestis (International Journal of Computing, 2014)
Measuring the position of a medical instrument inside the human body can be performed with various methods. One option is to measure the phase shift of the signal originating from a transmitter embedded into the tip of the medical instrument, determining its displacement with respect to a set of stationary receivers. The phase shift is converted into a low frequency voltage with the use of a Phased Locked Loop (PLL). This voltage can subsequently be converted into displacement, providing the position of the medical instrument in one (1D), two (2D) and three (3D) dimensions using trilateration. The instrument’s displacement can be defined in either the time or frequency domain. This paper presents a novel method for constant velocity displacement of the transmitter, using either the Locally Weighted Scatter-Plot Smoothing (LOWESS) curve fitting method or a Lomb-Scargle periodogram. The Lomb-Scargle periodogram is based on the least-squares power spectrum and can be used instead of waveform smoothing and measurement into the time domain, providing more precise and accurate measurement results as compared to LOWESS curve fitting method.